La rendición de cuentas en la pensión alimenticia y el interés superior del niño y adolescente - Ibarbo Crespo, Joel Andrés (2025)
The study analyzes the relevance of accountability in child support within the Organic Code of Childhood and Adolescence, aiming to ensure transparency in its administration. The lack of supervision has generated conflicts between parents and puts the well-being of minors at risk. Through theoretical and comparative analysis with regulations from Argentina and Uruguay, the need to include control mechanisms in Ecuador was identified. Survey and interview results revealed that 66% of respondents believe that child support is not used exclusively for minors, and 98% state that the absence of accountability generates conflicts. The implementation of periodic reports, supervised digital systems, and mediation processes is proposed. It is concluded that these measures would strengthen transparency and compliance with the best interests of the child. A legislative reform and effective supervision strategies are recommended.